PCR-BASED SPECIFIC DETECTION OF RALSTONIA SOLANACEARUM IN SOIL, SEED AND INFECTED PLANT MATERIAL - S. C. VANITHA,; S. UMESHA, (International Journal of Pharma and Bio Sciences, 2014)
DNA-based methods have provided powerful tools to identify and detect microorganisms with high sensitivity and specificity. PCR assay amplifies the DNA of bacterial pathogens, targeting the species-specific sequences in their genome. In the present study an efficient DNA isolation protocol and PCR based detection of bacterial wilt pathogen in soil, seed and infected plant materials has been described. The specific primers 759f/760r was successfully used to detect Ralstonia solanacearum from different sources and predicted 281-bp DNA fragment was obtained. In conclusion, the PCR-based detection method using R. solanacearum specific primer offers a rapid and sensitive method for unambiguous detection of this pathogen in soil, seed and infected tomato plant materials.